Method for preparing perovskite wafer based on physical hot pressing and application thereof

Through physical hot pressing and conductive polymer modification methods, the problems of poor phase stability and high defect density of perovskite crystals are solved, and efficient perovskite wafer preparation and excellent photoelectric properties are achieved.

CN119486556AActive Publication Date: 2025-02-18HEBEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411648995.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

There are problems of poor phase stability and high defect density in the traditional perovskite crystal preparation method, which limits its application in photodetectors.

Method used

The crystallinity and charge transport performance of perovskite wafers are improved by physical heat press assisted and conductive polymer modification methods.

Benefits of technology

Perovskite wafers with high phase stability and low defect density are achieved, improving their photoelectric performance and response speed in near-infrared photodetectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486556A_ABST
    Figure CN119486556A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a perovskite wafer based on physical hot pressing and application thereof. According to the method, physical hot pressing assistance and conductive polymer modification methods are adopted, that is, in the process of preparing the FAPbI3 wafer through a mechanical pressing method, an external heating field and conductive polymer modification are synchronously introduced. And the crystallinity of the wafer is improved by the thermal field with proper temperature, and finally the compact perovskite wafer with high crystallinity is obtained. The wafer obtained by the invention can be used for a high-sensitivity near-infrared (NIR) photoelectric detector, and shows excellent photoelectric properties in a near-infrared light band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite materials, and in particular to a method for preparing a high-efficiency perovskite wafer and an application thereof in a photoelectric detector by physical hot pressing assistance and conductive polymer modification. Background Art

[0002] Near-infrared (NIR) light detection technology plays an extremely important role in many fields such as medicine, bio-imaging and environmental monitoring. Traditional and commercial NIR photodetectors are usually made of inorganic narrow bandgap materials, such as silicon (Si), germanium (Ge), indium gallium arsenide (InGaAs), lead selenide (PbSe), polymers and graphene. In recent years, organic-inorganic hybrid perovskites have emerged in the field of NIR photodetectors due to their unique narrow bandgap, high absorption coefficient, long diffusion length and low exciton binding energy. The performance of perovskite-based NIR photodetectors mainly depends on their composition and microstructural characteristics, including lattice distortion, crystal orientation, grain size and morphology. Perovskite polycrystalline films are mainly prepared based on solution methods, and the solution preparation method has two main challenges: one is the ecological problems caused by phase impurities remaining in the solvent, poor product consistency, high solvent cost and toxicity; the other is that non-equilibrium crystallization in perovskite polycrystalline films will lead to defects and lattice stress, ion migration problems caused by uncontrollable crystal orientation and grain size inhomogeneity. At present, perovskite single crystals and quasi-single crystals prepared by techniques such as spatial confinement method and temperature rise method have achieved great success in the field of photodetectors and photovoltaic applications. However, these methods have low yields, long crystal growth processes, and require delicate external temperature conditions, which greatly limits their widespread application in photodetectors and solar cells.

[0003] FAPbI3 (formamidinium lead iodide) is an important perovskite material with a low band gap of about 1.45 eV, which is very suitable as a light absorption material. Its spectral response range has reached 850 nm in the near-infrared region, the energy range of sunlight, thereby optimizing the photoelectric conversion efficiency. The highest cell efficiency under laboratory conditions can exceed 27%. It maintains good thermal stability at high temperatures, reducing the risk of degradation in practical applications. At the same time, it has excellent light absorption ability and can effectively utilize solar energy. In addition, FAPbI3 has a high electron mobility, which helps to increase current output and reduce energy loss. In the field of detectors, FAPbI3 exhibits high sensitivity and wide wavelength range of light response, which is particularly suitable for imaging and photodetector applications under low light conditions. Its superior performance makes it a popular choice for the new generation of optoelectronic materials. Previous studies have shown that FAPbI3 thin-film photovoltaic devices prepared by solution method have high signal output and low noise current. However, research on perovskite photodetectors based on FAPbI3 is still very limited, mainly because FAPbI3 undergoes α→δ phase transition, which affects device performance. In addition, the presence of a large number of grain boundaries and high surface defect state density in perovskites will lead to severe non-radiative recombination and ion migration, limiting the practical application of perovskite optoelectronic devices. Therefore, the research focus of preparing FAPbI3 wafers is to suppress phase transitions and minimize defects.

[0004] The significance of preparing perovskite wafers is to promote the research and development of high-efficiency photovoltaic cells and photodetectors. Perovskite materials have attracted much attention due to their excellent optoelectronic properties, adjustable band gap and low-cost potential. At present, commonly used preparation methods include solution method, vapor deposition method, melting method, self-assembly method and mechanical pressing method.

[0005] The solution method is widely used because of its low cost and suitability for large-scale production, but its crystal quality and stability may have problems. The vapor deposition method can obtain high-quality thin films and is suitable for high-performance devices, but the equipment is complex and the cost is high. The melting method is suitable for the production of high-quality single crystal materials, but the process is complex and the energy consumption is high. The self-assembly method has innovative potential in material design, although the technology is not yet mature and industrialization is difficult. The mechanical pressing method applies pressure to the powder material to force it to form a dense crystal structure under high pressure. The advantage of this method is that it can quickly prepare large-sized crystals, while performing well in controlling the density and uniformity of the material. Compared with the solution method, the mechanical pressing method can avoid the influence of the liquid relative to the environment, thereby improving the stability of the material. However, this method may require high energy consumption and complex post-processing processes to ensure the purity and performance of the crystal.

[0006] In the patent number CN202310743832.1, "A method for preparing a large-size wafer-level perovskite semiconductor single crystal film", a new carbon dot-tin oxide interface layer technology is introduced for anchoring perovskite single crystal films to achieve large-area epitaxial growth. This method successfully obtained high-quality single crystal films with few defects and large areas. However, the patent does not address how to solve the problem of perovskite wafer phase stability. Summary of the invention

[0007] The present invention aims at the problems of poor perovskite crystal phase stability and high defect density in traditional processes, and provides a method for preparing perovskite wafers based on physical hot pressing and improving detection performance. The method adopts a method of physical hot pressing assistance and conductive polymer modification, that is, in the process of preparing FAPbI3 wafers by mechanical pressing, an external heating field and conductive polymer modification are simultaneously introduced. A thermal field with an appropriate temperature is used to improve the crystallinity of the wafer, and finally a perovskite wafer with high crystallinity and density is obtained. High crystallinity can resist phase change and is conducive to crystal phase stability. In addition, the chemical bonding of the conductive polymer can passivate defects on the perovskite grain boundary and improve its charge transfer performance. The combined effect of physical hot pressing assistance and conductive polymer modification realizes high-quality and large-size perovskite wafers. The wafer obtained by the present invention can be used for high-sensitivity near-infrared (NIR) photodetectors, and exhibits excellent photoelectric performance in the near-infrared light band.

[0008] The technical solution of the present invention is: A method for preparing a perovskite wafer based on physical hot pressing, the method comprising the following steps: Step 1: Preparation of perovskite microcrystalline powder: Dissolve methylamine iodide (FAI) and lead iodide (PbI2) in 2-methoxyethanol (2-ME), stir for 11-13 hours until completely dissolved, then filter, heat the filtrate to 120-150 °C and stir for 2-3 hours; obtain microcrystals after the reaction, filter again, wash and dry the microcrystals; finally, grind the prepared perovskite microcrystals into powder thoroughly; Among them, 10 ~ 20 mmol of methylamine iodide was added to every 15 mL of 2-methoxyethanol (2-ME), and the molar ratio of methylamine iodide (FAI) and lead iodide (PbI2) was 1:1; Step 2: Hot Pressing The conductive polymer and the perovskite microcrystalline powder were ground for 5-10 minutes, and then pressed at a temperature of 120-130 °C and a pressure of 18-22 MPa for 8-12 minutes to obtain a FAPbI3 perovskite wafer; The mass ratio of the polymer to the microcrystalline powder is 0.0005-0.0015; The perovskite wafer has a thickness of 0.9-1.1 mm; The conductive polymer is preferably polyaniline or polyethylene.

[0009] The perovskite wafer prepared by the method described is used to prepare FAPbI3 wafer photodetector, which exhibits excellent performance indicators and can meet the application requirements of near-infrared photodetection in many fields.

[0010] Using a metal-semiconductor-metal planar structure, a 80-100nm gold electrode is deposited on the surface of the perovskite wafer by thermal evaporation to form a photodetector.

[0011] The detector has an electrode spacing of 300~350 μm, an electrode length of 7.4~7.5 mm, and an electrode width of 350~400 μm.

[0012] The essential features of the present invention are: This method combines the traditional mechanical pressing method with a physical thermal field (120°C hot pressing) and chemical bonding (conductive polyaniline), overcoming the limitations of traditional methods in terms of crystallization control and defect density control. At the same time, this method can achieve the preparation of inch-level perovskite wafers, and the prepared wafers have the characteristics of high crystal quality, high phase stability, high absorption efficiency, and low defect density, providing a basis for the large-scale production of large-area perovskite optoelectronic integrated devices in the future.

[0013] The preparation principle of the present invention is as follows: Physical hot pressing stabilizes the crystal phase: During the preparation process, hot pressing at 120°C plays a key role in stabilizing the FAPbI3 crystal phase. The hot pressing process can cause the perovskite powder to undergo physical changes under high temperature and pressure, causing the grains to re-fuse and grow, thereby reducing the number of grain boundaries and improving crystallinity. This physical effect helps to suppress the α→δ phase transition of FAPbI3, ensuring that the wafer has a stable crystal structure, laying the foundation for subsequent high-performance photoelectric detection.

[0014] Polymer chemical bonding passivates defects: During the hot pressing process, chemical bonding is formed between the conductive polymer and FAPbI3. This interaction not only reduces the formation of defects, but also effectively inhibits ion migration. At the same time, the polymer is evenly distributed in the wafer, can fill the grain boundaries, passivate grain boundary defects, thereby reducing the probability of non-radiative recombination, and further enhancing the overall stability and optoelectronic performance of the wafer.

[0015] The beneficial effects of the present invention are: High phase stability: The method of the present invention successfully overcomes the problems of crystal phase impurities and high-density defects caused by the traditional solution growth method for preparing perovskite, and ensures that the FAPbI3 wafer has excellent phase stability through the synergistic effect of physical hot pressing and chemical modification. This allows the wafer to maintain a stable crystal structure and optoelectronic properties under long-term use and different environmental conditions.

[0016] Excellent photoelectric performance: The FAPbI3 wafer photodetector prepared based on the present invention exhibits excellent performance indicators. The perovskite wafer detector based on physical hot pressing assistance and conductive polymer modification has a fast response time and light switch cycle operation stability to 810 nm near-infrared light (the best rise time can reach 6 milliseconds, and the best fall time can reach 9.5 milliseconds). These performance parameters are better than the same component perovskite thin film photodetector prepared by the traditional solution method (the rise time is generally 72 milliseconds, and the fall time is generally 93 milliseconds), and can meet the application requirements of near-infrared photodetection in many fields.

[0017] Large-scale preparation potential: The preparation method of the present invention is simple and easy to implement, and has a high degree of repeatability. By optimizing the process parameters, large-scale preparation of FAPbI3 wafers can be achieved, providing a reliable material basis for the development of future integrated perovskite optoelectronic devices. This will help promote the widespread application of perovskite materials in the optoelectronic field, such as medical imaging, biological detection, environmental monitoring, etc.

[0018] The present invention adopts the strategies of hot pressing (120 °C and 20 MPa) and chemical bonding (conductive polymer), effectively solving the problem of crystal phase impurities and high-density defects caused by the traditional solution growth method for preparing perovskite, and improving the phase stability of FAPbI3 wafers. The FAPbI3 wafer photodetector prepared based on the present invention exhibits excellent photoelectric performance. At the same time, the method of the present invention is simple and easy to implement, has strong repeatability, and can realize the large-scale preparation of FAPbI3 wafers, providing a scalable material basis for future integrated perovskite photoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of FAPbI3 perovskite wafer photodetector; Figure 2 This is a cross-sectional scanning electron microscope image of the physically hot-pressed and polymer-modified FAPbI3 perovskite wafer obtained in Example 1 at a magnification of 1500 times at a scanning voltage of 3 kV; Figure 3 This is a cross-sectional scanning electron microscope image of the FAPbI3 perovskite wafer obtained in Comparative Example 1 at a magnification of 1500 times at a scanning voltage of 3 kV; Figure 4The transient response time test of the physically hot pressed and polymer modified FAPbI3 perovskite wafer detector obtained in Example 1 to 810 nm near-infrared light under 1 V bias; Figure 5 The transient response time test of the FAPbI3 perovskite wafer detector obtained in Comparative Example 1 to 810 nm near-infrared light under a bias voltage of 1 V; Figure 6 The transient response time test of the FAPbI3 perovskite thin film detector obtained in Comparative Example 2 to 810 nm near-infrared light under a bias voltage of 1 V; Figure 7 The switching cycle response test of the physical hot pressing and polymer-modified FAPbI3 perovskite wafer detector obtained in Example 1 to 810 nm near-infrared light under 1 V bias; Figure 8 The switching cycle response test of the FAPbI3 perovskite wafer detector obtained in Comparative Example 1 to 810 nm near-infrared light under a bias voltage of 1 V; Fig. 9 The switching cycle response test of the FAPbI3 perovskite thin film detector obtained in Comparative Example 2 to 810 nm near-infrared light under a bias voltage of 1 V; Fig.10 The transient response time test of the physically hot pressed and polymer modified FAPbI3 perovskite wafer detector obtained in Example 2 to 810 nm near-infrared light under 1 V bias; Fig.11 The transient response time test of the physically hot-pressed and polymer-modified FAPbI3 perovskite wafer detector obtained in Example 3 to 810 nm near-infrared light under a bias of 1 V. DETAILED DESCRIPTION

[0020] In order to simultaneously solve the phase stability and defect problems in perovskite wafers and prepare large-area perovskite films or wafers, this paper proposes a new strategy: high-quality inch-scale large-size FAPbI3 wafers for high-sensitivity near-infrared light detection are achieved through hot pressing and chemical bonding of conductive polymers. This process is the first universal preparation process for large-area wafers. The polymer is an intrinsically conductive polymer with tunable conductivity, allowing efficient charge transport within the FAPbI3 wafer photodetector with high light response speed and sensitivity. Physical hot pressing can suppress phase transitions and stabilize the FAPbI3 crystal phase, while chemical bonding of conductive polymers can passivate defects on grain boundaries. Finally, stable and fast near-infrared light detection can be achieved through FAPbI3 wafers based on physical hot pressing and conductive polymer modification. With this approach, we not only solve the problem of poor phase stability in perovskite wafers, but also significantly improve their optoelectronic properties, providing a new solution for efficient near-infrared light detection.

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention: Embodiment 1: Fabrication of FAPbI3 perovskite wafer detectors modified by physical hot pressing and conductive polymer Step (1): Preparation of FAPbI3 perovskite microcrystalline powder Solution preparation: Accurately weigh 15 mmol of methylamine iodide (FAI) and 15 mmol of lead iodide (PbI2), place them in 15 mL of 2-methoxyethanol (2-ME), and stir continuously for 12 h at a constant temperature of 50 °C using a magnetic stirrer to ensure that the two substances are fully dissolved and evenly mixed to form a uniform solution.

[0022] Reaction and crystallization: Filter the above solution through filter paper to remove possible insoluble impurities and obtain a pure precursor solution. Transfer the filtered solution to an oil bath, set the oil bath temperature to 120°C, and react for 2 hours under magnetic stirring. During the reaction, the substances in the solution gradually undergo chemical reactions to form a large number of black FAPbI3 perovskite microcrystals.

[0023] Post-treatment: After the reaction is completed, the solution is filtered again to separate the generated microcrystals from the solution. Then, the microcrystals are washed with 2-ME and isopropyl alcohol (IPA) in turn to remove impurities and unreacted substances remaining on the surface. Finally, the washed microcrystals are placed in a vacuum oven at 100°C for drying to completely remove moisture and residual solvent. The dried FAPbI3 perovskite microcrystals are ground into 400 mesh powder for 10 minutes for subsequent processing.

[0024] Step (2): Physical hot pressing and conductive polymer modified pressing molding Take a certain amount of polyaniline, grind it thoroughly into fine powder, and then screen it through a 1000 mesh sieve to obtain a polymer powder with uniform particle size. Accurately weigh 1 mg of sieved polyaniline and mix it with 1 g of FAPbI3 powder, and grind it again in a mortar for 10 minutes to make the polyaniline evenly distributed in the perovskite powder. Put the mixed powder into a mechanical pressing device and hot press it again at 120°C and 20MPa for 10 minutes. During the hot pressing process, the powder particles deform and densify under high temperature and pressure, initially forming perovskite wafers with a thickness of 1 mm and a diameter of 2 cm.

[0025] Step (3): Preparation of metal counter electrode Place the perovskite wafer into the mask of the thermal evaporator. When the gold particles on the evaporation boat are at 5*10 -4 When the vacuum degree is 1.3 Pa, the evaporation rate is controlled at 0.05 nm / s until a gold electrode with a thickness of 80 nm is deposited, completing the preparation of the perovskite wafer detector. Figure 1 As shown, the electrode gap is 300μm, the electrode length is 7.4 mm, and the electrode width is 300μm. The wafer detector has a metal-semiconductor-metal structure. When light shines on the wafer detector, the perovskite layer absorbs light and generates electron-hole pairs. Due to the close contact between the metal layer and the semiconductor layer, and the good conductivity of the metal layer, these electrons and holes are extracted into the positive and negative metal electrodes respectively to form current.

[0026] Comparative Example 1: Preparation of FAPbI3 perovskite wafer detector by physical hot pressing Step (1): Preparation of FAPbI3 perovskite microcrystalline powder Exactly the same as the above-mentioned embodiment 1.

[0027] Step (2): Pressing The FAPbI3 perovskite microcrystalline powder was transferred to a customized mechanical pressing device, where a pressure of 20 MPa and a temperature of 120°C were applied to the powder for 10 minutes to form a perovskite wafer with a thickness of 1 mm and a diameter of 2 cm.

[0028] Step (3): Preparation of metal counter electrode Exactly the same as the above-mentioned embodiment 1.

[0029] Comparative Example 2: Preparation of FAPbI3 perovskite thin film detectors Step (1): Preparation of FAPbI3 perovskite film 1.6 mmol of methylamine iodide (FAI) and lead iodide (PbI2) were dissolved in 1 mL of dimethylformamide and dimethyl sulfoxide (8:2) and stirred continuously for 2 h at a constant temperature of 25 °C using a magnetic stirrer to form a uniform perovskite solution. Under nitrogen conditions, the perovskite solution was coated on a glass substrate and then spin-coated in one step using a spin coater at 5000 rpm for 30 seconds, followed by vacuum flash evaporation for 30 seconds. The film was then heated at 100 °C for 30 minutes. Finally, a FAPbI3 perovskite film was obtained.

[0030] Step (2): Preparation of metal counter electrode Exactly the same as the above-mentioned embodiment 1.

[0031] The following will explain the morphology and performance improvement effects of the FAPbI3 perovskite wafer detector modified by physical hot pressing and conductive polymer in the present invention based on experimental data.

[0032] Morphological characterization and analysis Figure 2 and Figure 3 The following are scanning electron microscope images of Example 1 and Comparative Example 1 at a scanning voltage of 3 kV and a magnification of 1500 times. Figure 3 In terms of seeing Figure 2 The grains of FAPbI3 perovskite wafers modified by physical hot pressing and conductive polymers tend to increase. This shows that after such physical hot pressing and conductive polymer modification, the perovskite powder undergoes physical changes under high temperature and high pressure, causing the grains to re-fuse and grow, thereby reducing the number of grain boundaries and improving crystallinity. The grain size of the wafers after hot pressing and polymer modification is significantly increased, the grain boundaries are reduced, and the surface is smoother, which proves the effectiveness of physical hot pressing and chemical modification in improving wafer quality.

[0033] Performance testing and analysis Figure 4 , Figure 5 and Figure 6 The transient response time of Example 1, Comparative Example 1 and Comparative Example 2 to 810 nm near-infrared light under 1 V bias is tested. The results show that the FAPbI3 perovskite wafer detector modified by physical hot pressing and polymer effectively improves the response speed to near-infrared light, increasing the response time from 16 milliseconds to 6 milliseconds. Compared with Comparative Examples 1 and 2, the detector prepared based on the present invention increases the response time by 2.6 times and 12 times, respectively.

[0034] Figure 7 , Figure 8 and Fig. 9The switching cycle response tests of Example 1, Comparative Example 1 and Comparative Example 2 to 810 nm near-infrared light under 1 V bias are shown. The results show that the FAPbI3 perovskite wafer detector modified by physical hot pressing and polymer has more stable light switching cycle stability, lower dark current and more stable baseline drift. Compared with Comparative Examples 1 and 2, the detector prepared based on the present invention produces a higher and more stable output current to near-infrared light. The improvement in electrical performance can be attributed to the formation of chemical bonds between the polymer and the perovskite, thereby passivating defects and inhibiting carrier recombination.

[0035] Embodiment 2: The other steps are the same as in Example 1, except that pressing for 10 minutes is replaced by pressing for 12 minutes; The device performance obtained is similar to that of Example 1, such as Fig.10 As shown; Embodiment 3: The other steps are the same as in Example 1, except that the hot pressing temperature of 120°C is replaced by 130°C; The device performance obtained is similar to that of Example 1, such as Fig.11 shown.

[0036] The present invention successfully prepares large-sized, high-phase-purity perovskite wafers. The physical hot pressing technology is used to stabilize the perovskite crystal phase, and the chemical modification of the polymer is combined to passivate the defects. The synergistic effect of the two improves the response speed and detection capability of the wafer photodetector. The wafer photodetector has extremely high photoelectric response and operation stability in the near-infrared band, meeting the needs of efficient photodetection applications.

[0037] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a perovskite wafer based on physical hot pressing, characterized in that the method comprises the following steps: Step 1: Preparation of perovskite microcrystalline powder: Dissolve methylamine iodide (FAI) and lead iodide (PbI2) in 2-methoxyethanol (2-ME), stir for 11-13 hours until dissolved, then filter, heat the filtrate to 120-150 °C and stir for 2-3 hours; obtain microcrystals after the reaction, filter again, wash and dry the microcrystals; finally grind the prepared perovskite microcrystals into powder; in, Add 10-20 mmol of methylamine iodide to every 15 mL of 2-methoxyethanol (2-ME), and the molar ratio of methylamine iodide (FAI) to lead iodide (PbI2) is 1:1; Step 2: Hot Pressing The conductive polymer and the perovskite microcrystalline powder were ground for 5-10 minutes, and then pressed at a temperature of 120-130 °C and a pressure of 18-22 MPa for 8-12 minutes to obtain a FAPbI3 perovskite wafer; The mass ratio of the polymer to the microcrystalline powder is 0.0005-0.0015.

2. The method for preparing a perovskite wafer based on physical hot pressing as described in claim 1, characterized in that the thickness of the perovskite wafer is 0.9~1.1 mm.

3. The method for preparing perovskite wafers based on physical hot pressing as described in claim 1, characterized in that the conductive polymer is polyaniline or polyethylene.

4. Application of the perovskite wafer prepared by the method according to claim 1, characterized in that it is used to prepare FAPbI3 wafer photodetector.

5. The use according to claim 4, characterized in that Using a metal-semiconductor-metal planar structure, a 80-100 nm gold electrode is deposited on the surface of the perovskite wafer by thermal evaporation to form a photodetector; The detector has an electrode spacing of 300~350 μm, an electrode length of 7.4~7.5 mm, and an electrode width of 350~400 μm.

Citation Information

Patent Citations

  • Method for preparing large-area perovskite thin film based on two-step method and application thereof

    CN112687804A

  • Perovskite metal halide zero-dimensional quantum dot / polymer composite material and preparation method thereof, and application of organic amine salt

    CN114149641A

  • Direct type X-ray detector based on perovskite wafer and preparation method thereof

    CN115000304A

  • Solar cell based on conductive polymer modified perovskite / carbon electrode interface

    CN116546829A